Historical Background of Artcle 356 of Indian Constitution: The Historical Evolution of Article 356 in the Indian Constitution (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The power of the President to impose President’s Rule in States is a legacy of the British Colonial rule in India. The British Government introduced this rule so that they might fulfill their imperial interests. The founding fathers of the Constitution of India were also alive to the fact that several regions of the country did not have deep-rooted conventions of parliamentary form of government and as a result failure of constitutional machinery in such a State could not be ruled out as a possibility. In a way, this was a reflection of the times. The nation at this time was passing through a critical period in its history in the wake of partition, communal riots and the disintegration of the country. The strength of the Union was perceived as the need of the hour and this power was provided to the President, who is directed by the Union Council of Ministers.The process of centralisation of power with the Centre is a legacy of British colonial rule in India. The British East India Company centralised the powers with the Center to control its Indian regions. The Regulating Act, 1773, started the Centralisation of administration in India, and the Charter Act of 1883 strengthened the centralisation of power. From the earliest 1773 phase until independence, India was governed as a unitary and not as a federal state. In attempt to satisfy the demands of princely states and the Muslim demands for greater autonomy, the British introduced a set of political reforms in 1935.[1]Historically, the proximate origin of the President’s Rule in traced back to the Government of India Act, 1935. This Act, for the first time, specifically empowered the Governors under Section 93 with emergency powers which they could use for taking over the provincial administration. Article 356 has its ancestry in Section 93 of the Government of India Act, 1935